Impact of chronic kidney disease on left atrial appendage occlusion for stroke prevention in patients with atrial fibrillation. (15th March 2016) - Kefer, Joelle; Tzikas, Apostolos; Freixa, Xavier; Shakir, Samera; Gafoor, Sameer; Nielsen-Kudsk, Jens Erik; Berti, Sergio; Santoro, Gennaro; Aminian, Adel; Landmesser, Ulf; Nietlispach, Fabian; Ibrahim, Reda; et al.
Abstract: Background: Left atrial appendage occlusion (LAAO) using the Amplatzer cardiac plug (ACP) is a preventive treatment of atrial fibrillation related thromboembolism. Aim: To assess the safety and efficacy of LAAO in patients with chronic kidney disease (CKD). Methods: Among the ACP multicentre registry, 1014 patients (75 ± 8 yrs) with available renal function were included. Results: Patients with CKD (N = 375, CHA2DS2-VASc: 4.9 ± 1.5, HASBLED: 3.4 ± 1.3) were at higher risk than patients without CKD (N = 639, CHA2DS2-VASc: 4.2 ± 1.6, HASBLED: 2.9 ± 1.2; p < 0.001 for both). Procedural (97%) and occlusion (99%) success were similarly high in all stages of CKD. Peri-procedural major adverse events (MAE) were observed in 5.1% of patients, 0.8% of death, with no difference between patients with and those without CKD (6.1 vs 4.5%, p = 0.47). In patients with complete follow-up (1319 patients years), the annual stroke + transient ischaemic attack (TIA) rate was 2.3% and the observed bleeding rate was 2.1% (62 and 60% less than expected, similarly among patients with and those without CKD). Kaplan–Meier analysis showed a lower overall survival (84 vs 96% and 84 vs 93% at 1 and 2 yrs. respectively; p < 0.001) among patients with an eGFR < 30 ml/min/1.73 m 2 . Conclusion: LAAO using the ACP has a similar procedural safety among CKD patients compared to patients with normal renal function. LAAO with ACP offers a dramatic reduction of stroke + TIA rate and of bleeding rate persistent in all stages of CKD, as compared to the expected annual risk.